XALÍQ PEDAGOGIKASÍNDA BALALALARDÍ TÁRBIYALAWDA DENE TÁRBIYASÍNÍŃ ÁHMIYETI - Zarımbetova, G. (SCIENCE and SOCIETY, 2020)
The article describes the historical methods of Karakalpak folk education. There are analyzed specific types of physical education of children in national Pedagogics. The author also shows the relationship between types of education.
Keywords: pedagogics; folk pedagogics; education of a children; manners and behavior; physical education; parents